Means of Hesitation in Conversation - Pokorná, Kateřina (Univerzita Pardubice, 2018)
This bachelor thesis deals with means that express speakers' hesitation or uncertainty. The first chapter of the theoretical part introduces main characteristics of conversation. It focuses mainly on those that distinguish spoken language from written language. A great deal of attention is then devoted to the means that express speakers' uncertainty and hesitation. It discusses their forms and functions. In the practical part, findings obtained in the theoretical part are applied to the analysis of conversations, in order to map the frequency of means of hesitation in formal and informal conversations.
Prostředky váhání v konverzaci
Keywords: konverzace; váhání; vyplněné pauzy; opakování; opravné struktury; conversation; hesitation; filled pauses; repetitions; speech repairs